The Power of Employee Voice: A Key to Building a Culture of Ethics and Engagement in the Workplace - Kazeem Adebayo Oladimeji (Universitas Sultan Ageng Tirtayasa, 2024)
This study investigated the relationship between employee voice, ethical behaviour, employee commitment, and engagement in the public service. Using a purposive sampling technique of 125 employees as samples from five selected ministries and agencies in the Kwara State Civil Service in Nigeria, a questionnaire was administered and analysed using Structural Equation Modelling—Partial Least Squares (SEM-PLS). The study found that employee voice positively influenced ethical behaviour, employee commitment, and employee engagement. Ethical behaviour, in turn, had a positive effect on employee commitment and engagement. The study also revealed that employee commitment partially mediated the relationship between employee voice and employee engagement. The results suggest that empowering employees to speak up and provide feedback on ethical issues can lead to a greater sense of commitment and engagement. The study recommends that organisations prioritise ethical behaviour and integrity in their operations, provide training and support to help employees feel more comfortable speaking up, and create a culture of transparency and accountability. The study also highlights the importance of promoting employee commitment to improve employee engagement through professional development opportunities, recognition and rewards, and a supportive work environment.